Implementation of a Monitoring and Evaluation System to Improve the Efficiency of Goods Delivery at Ninja Express in Gunungsitoli City - Andika Pranata Telaumbanua; Palindungan Lahagu; Eliyunus Waruwu (JURNAL ECONOMINA, 2026)
This study aims to examine the implementation of a monitoring and evaluation system in improving the efficiency of goods delivery at Ninja Express in Gunungsitoli, to assess the current state of the goods delivery process, and to identify the challenges faced in that process. This study employs a qualitative approach, with the researcher serving as the key instrument. Data were collected through observation, interviews, and document analysis, then analyzed using an interactive model comprising data collection, data reduction, data presentation, and drawing conclusions. The research variables were measured based on five monitoring and evaluation indicators: inputs, processes, outputs, outcomes, and impacts. The research results show that the implementation of the monitoring and evaluation system at Ninja Express in Gunungsitoli is supported by adequate hardware and software as well as trained human resources. Structured implementation through SOPs and real-time tracking technology has successfully increased delivery efficiency by approximately 15–20 percent, reduced operational errors, and improved process transparency and customer satisfaction. In the long term, this system also contributes to lower operating costs and increased company productivity. This study recommends enhancing human resource training, strengthening internal communication, optimizing technology, and strengthening risk management and compliance to maintain sustainable operational efficiency.